kONSEP IMPLEMENTASI PENGEMBANGAN TOD PADA SIMPUL TRANSPORTASI MODA KERETA API (Studi Kasus: Provinsi Banten, Indonesia) - Hera Zetha Rahman; Azaria Andreas; Akhmad Dofir; Perdana Miraj Sejatiguna; Nina Kade Nirmala (Universitas Trisakti, 2021)
A train is a mass transportation means that can carry passengers or goods on a large scale, so that the Indonesian people use it as a means of transportation both within cities and intercity/ Along with this, the train station is the main requirement needed in the movement of the rail transportation mode. Apart from the main function of the station as a place for passengers to get on or off, stations can be developed into centers of urban activities by maximizing the use of space at the station and the utilization of the surrounding space which is integrated with the development of properties high density and other supporting facilities. To realize this, an effort is needed to maximize the potential for station development through the Transit Oriented Development (TOD) approach. The development of TOD at a railway station can create an ideal distance or radius from a transportation node to occupancy, creating lower cost, time and energy efficiency so as to improve the quality of life in urban areas, and it is hoped that it can reduce the maintenance costs of the station itself through additional functions that can generate revenue. In order to optimize the function of railway stations, especially in urban areas, this study was conducted to create a concept for regional development with the concept of TOD based on railway stations. This study used a qualitative approach with the study area located in Banten Province (outside the BPTJ working area), and data collection was carried out using purposive sampling method. The result is a station that has the potential to be developed into a transit-based area in Banten Province is the Serang Station.